Algorithm CFP-SFP with parallel processing - Kujawiak, Mariusz (Studia Informatica. System and information technology, 2008)
Existing algorithms for finding association rules do not implement parallel processing. This paper proposes CFP-SFP (Creating Frequent Patterns with Set from Frequent Patterns algorithm with parallel processing. The research involves running CEP-SEP algorithm with one thread and a dozen or so threads that are executed simultaneously. The research was conducted on a computer with one processor and dual-core processor.